2018
DOI: 10.3390/md16120512
|View full text |Cite
|
Sign up to set email alerts
|

Potential Usefulness of a Wakame/Carob Functional Snack for the Treatment of Several Aspects of Metabolic Syndrome: From In Vitro to In Vivo Studies

Abstract: Metabolic syndrome (MetS) greatly increases the risk of cardiovascular diseases and type 2 diabetes mellitus. The aim of this study was to evaluate the efficacy of functional snacks containing a combination of wakame (W) and carob pod (CP) flours in reducing markers associated with MetS. The mechanisms of action underlying these effects were also evaluated. In vitro approaches were carried out in mature 3T3-L1 adipocytes and RAW 264.7 macrophages treated with different doses of extracts from W, CP, or a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…In visceral adipose tissue, the improved insulin resistance was associated with a decreased expression of pro-inflammatory markers such as IL-1β, TNF-α, and MCP-1 and with a decreased macrophage infiltration. Likewise, other authors have reported a direct anti-inflammatory effect of carob pod in LPS-stimulated macrophages [27,31]. Like in AT, we also found a lower gene expression of MCP-1 and decreased macrophage infiltration in gastrocnemius explants from CSAT+ ® -supplemented mice, although the mRNA levels of pro-inflammatory cytokines were unchanged among experimental groups.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In visceral adipose tissue, the improved insulin resistance was associated with a decreased expression of pro-inflammatory markers such as IL-1β, TNF-α, and MCP-1 and with a decreased macrophage infiltration. Likewise, other authors have reported a direct anti-inflammatory effect of carob pod in LPS-stimulated macrophages [27,31]. Like in AT, we also found a lower gene expression of MCP-1 and decreased macrophage infiltration in gastrocnemius explants from CSAT+ ® -supplemented mice, although the mRNA levels of pro-inflammatory cytokines were unchanged among experimental groups.…”
Section: Discussionsupporting
confidence: 84%
“…In vivo, our results show that supplementation with CSAT+ ® does not affect body weight gain or adiposity in mice fed a HFHS diet. Likewise, other authors have reported that treatment with carob pod affects neither body weight, nor fat mass in vivo [27]. However, it exerts a strong delipidating effect in vitro on adipocyte cultures [31] and in vivo reduces liver triacylglycerol levels in obese rats [45] and in rabbits with hypercholesterolemia [28].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These authors pointed out the need of a long-term study to investigate the potential use of A. nodosum -enriched bread in overweight subjects and deepen its mechanism of action. Another study investigated the effect of a combination of U. pinnatifida and Ceratonia siliqua L. in functional snacks [ 143 ]. In a rat model, the anti-inflammatory and anti-hypertensive effects of these algal-enriched snacks were observed, suggesting its potential use for MS management.…”
Section: Brown Seaweeds As Functional Food Ingredients For the Manmentioning
confidence: 99%
“…As far as mature adipocytes are concerned, only one study has been reported so far addressing the effects of macroalgae extracts on TG accumulation. In such study, Martínez-Villaluenga et al [18] analyzed the effect of two doses of an extract from the brown macroalgae Undaria pinnatifida. 3T3-L1 mature adipocytes were treated on day 8 after differentiation for 24 h with 1 or 10 µg/mL of the extract.…”
Section: In Vitro Studiesmentioning
confidence: 99%